2004
DOI: 10.1200/jco.2004.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel Combined With Trastuzumab Is an Active Regimen in HER-2 3+ Overexpressing and Fluorescent In Situ Hybridization–Positive Metastatic Breast Cancer: A Multi-Institutional Phase II Trial

Abstract: Trastuzumab plus docetaxel is an active and well-tolerated regimen in women with HER-2 3+ overexpressing or FISH-positive metastatic breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
5

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(47 citation statements)
references
References 25 publications
1
41
0
5
Order By: Relevance
“…On the contrary, weekly docetaxel in combination with trastuzumab seems to be more toxic, with two independent studies reporting that approximately one quarter of cases were withdrawn because of severe toxicity [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, weekly docetaxel in combination with trastuzumab seems to be more toxic, with two independent studies reporting that approximately one quarter of cases were withdrawn because of severe toxicity [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, several phase II studies of trastuzumab in combination with docetaxel, as first-or as second-line treatment for patients with HER2 -overexpressing MBC, have been reported with RR ranging from 45 to 72% (Burris, 2001;Esteva et al, 2002;Montemurro et al, 2004;Tedesco et al, 2004). More recently, the results of a randomised phase II trial evaluating the activity and the efficacy of trastuzumab plus docetaxel in the first-line treatment of HER2 -overexpressing MBC patients have been reported (Marty et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In previously treated patients with MBC, other phase II studies have demonstrated response rates of 11 to 15% with trastuzumab as a monotherapy (6,7) and 24 to 65% for combinations of trastuzumab with platinum salts (8), taxanes (10,13,14,24), vinorelbine (25,26), or a triplet of trastuzumab with taxanes and platinum salts (27). Preliminary analysis of a randomized study of trastuzumab and paclitaxel vs the same regimen in combination with carboplatin demonstrated an improvement in time to progression with the triplet association The optimal trastuzumab-based chemotherapy regimen has not been identified, even though there is a trend favoring weekly schedules of cytotoxic agents compared to standard dosages given every 3-4 weeks (32).…”
Section: Discussionmentioning
confidence: 99%
“…This led to the development of alternative trastuzumab-based combinations for HER-2/neu-positive MBC. Several studies have assessed the antitumoral activity and tolerability of the trastuzumab and taxanes combination, an active first-line therapy for this setting of patients (10)(11)(12)(13)(14). However, when first-line chemotherapy fails, non-crossresistant treatments with minimal toxic effects that could be easily administered on an outpatient basis are warranted.…”
Section: Introductionmentioning
confidence: 99%